1999
DOI: 10.1590/s0101-81751999000600020
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza de mamíferos de grande e médio porte do Parque Nacional da Serra do Divisor (Acre, Brasil)

Abstract: ABSTRACT. The richness ofthe large and medium-sized mammals ofthe Serra do Divisor National Park (Acre, Brazil). The objective ofthe present study was to characterize the richness (number of species) of large and medium-sized mammals, and the antropic threats in the Parque Nacional da Serra do Divisor (PNSD). ln 31 days data were collected ÚlI"ough direct observations or evidences (bones, hairs, vocalizations and tracks) along pre-existing trails distributed in different types ofvegetation. Wild mammals captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
1
15
0
4
Order By: Relevance
“…Despite their great ecological importance, large and medium-sized mammals have been poorly studied in the state of Acre, and the available works focused on rapid surveys (e.g. Calouro 1999), assessments of the effects of subsistence hunting on mammals (e.g. Calouro and Marinho-Filho 2005;Rosas and Drumond 2007), and studies of primate autoecology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their great ecological importance, large and medium-sized mammals have been poorly studied in the state of Acre, and the available works focused on rapid surveys (e.g. Calouro 1999), assessments of the effects of subsistence hunting on mammals (e.g. Calouro and Marinho-Filho 2005;Rosas and Drumond 2007), and studies of primate autoecology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on plants (Silveira et al 1997;Goldenberg and Meirelles 2011), mammals (Calouro 1999), birds (Whitaker and Oren 1999;Guilherme 2001;Guilherme and Borges 2011), amphibians (Lima et al 2007) and some arthropod groups (Morato 2001;Villarreal-Manzanilla and Pinto-Da-Rocha 2006;Oliveira et al 2009;Carvalho and Esposito 2010) suggests a large diversity and endemism in forested areas of Acre. However, the distribution of terrestrial invertebrates is relatively unknown (Morato et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the existence of areas with a high biodiversity and high degree of endemism in this state (Souza et al 2003) for plants (Prance 1973;Silveira et al1997;Goldenberg and Meirelles 2011), mammals (Calouro 1999), birds (Haffer 1987;Whitaker and Oren 1999;Guilherme 2001;Guilherme and Borges 2011), amphibians (Lima et al2007), some insect orders (Brown 1991), including ants (Oliveira et al 2009;Miranda et al 2012), paper wasps (Morato 2001), lepidopterans (Brow, 1977, coleopterans (Vaz-de-Melo 1999), dipterans (Carvalho and Esposito 2010) and other arthropods, such as Opiliones (Villarreal-Manzanilla and Pinto-Da-Rocha 2006). Yet, very little is known about the diversity of social wasps in this part of the Amazon, since only two surveys carried out in Acre included social wasps (Richards 1978;Moratoet al2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian Amazon rainforest has one of the greatest biodiversities in the world, including the greatest diversity of social wasps (Silveira 2002;Somavilla et al 2014;Barbosa et al 2016). The western Amazon (which includes parts of Bolivia, Colombia, Ecuador, Peru, and western Brazil) is one of the most biodiverse regions of the planet for many taxa (Brown 1977(Brown , 1991Calouro 1999;Carpenter and Marques 2001;Ceballos and Ehrlich 2006;Carvalho and Esposito 2010;Barbosa et al 2016). The region maintains large areas of intact tropical forest and stable climate conditions, which, combined with richer soils originated from Andean sediments, is likely related to the west-east diversity gradient that has been found for some groups of Amazonian organisms, such as trees and mammals (Ceballos et al 2005;Hoorn et al 2010;Cheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%